2002
DOI: 10.1002/ar.10060
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐, glycine‐, and glutamate‐immunoreactive bouton profiles in apposition to neurons of the central cervical nucleus in the rat

Abstract: The neurons of the central cervical nucleus (CCN) convey information about the position and movements of the head, and receive excitatory input from dorsal neck muscles and the labyrinth. Both of these afferent sources form glutamatergic synaptic contacts with CCN neurons. However, these sensory afferent sources can also inhibit CCN neurons. To further elucidate the synaptic organization, we made an electron microscopic investigation, identifying and evaluating the relative frequency of bouton profiles contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Projections from upper cervical segments to lateral, medial and descending vestibular nuclei also originate from the CeCv (Carleton and Carpenter, 1983;Bankoul and Neuhuber 1992;Matsushita et al, 1995;Xiong and Matsushita, 2001). Calretinin and calmodulin (Ren andRuda, 1994), enkephalin (Ikeda et al, 1995), GABA and glycine (Ragnarson et al, 2002), glutamate (Ornung et al, 1995;Ragnarson et al, 2002;Persson et al, 2006) and parvalbumin (Ren and Ruda, 1994) are found within neurons of the CeCv. Calretinin and calmodulin (Ren andRuda, 1994), enkephalin (Ikeda et al, 1995), GABA and glycine (Ragnarson et al, 2002), glutamate (Ornung et al, 1995;Ragnarson et al, 2002;Persson et al, 2006) and parvalbumin (Ren and Ruda, 1994) are found within neurons of the CeCv.…”
Section: Central Cervical Nucleusmentioning
confidence: 99%
“…Projections from upper cervical segments to lateral, medial and descending vestibular nuclei also originate from the CeCv (Carleton and Carpenter, 1983;Bankoul and Neuhuber 1992;Matsushita et al, 1995;Xiong and Matsushita, 2001). Calretinin and calmodulin (Ren andRuda, 1994), enkephalin (Ikeda et al, 1995), GABA and glycine (Ragnarson et al, 2002), glutamate (Ornung et al, 1995;Ragnarson et al, 2002;Persson et al, 2006) and parvalbumin (Ren and Ruda, 1994) are found within neurons of the CeCv. Calretinin and calmodulin (Ren andRuda, 1994), enkephalin (Ikeda et al, 1995), GABA and glycine (Ragnarson et al, 2002), glutamate (Ornung et al, 1995;Ragnarson et al, 2002;Persson et al, 2006) and parvalbumin (Ren and Ruda, 1994) are found within neurons of the CeCv.…”
Section: Central Cervical Nucleusmentioning
confidence: 99%